An Improved Dehydroepiandrosterone-Induced Rat Model of Polycystic Ovary Syndrome (PCOS): Post-pubertal Improve PCOS's Features - Kim, Eun-Jeong; Jang, Minhee; Choi, Jong Hee; Park, Kyoung Sun; Cho, Ik-Hyun (Frontiers in Endocrinology, 2018)
Complete animal models investigating the pathogenesis and treatment of polycystic ovarian syndrome (PCOS) are not completely established. Although dehydroepiandrosterone (DHEA)-induced pre-pubertal rat model for PCOS has been widely used, the model exhibits weaknesses such as decreased ovary weight. Here, we report improved DHEA-induced PCOS model addressing the limitations of the pre-pubertal model. The 21-day-old (pre-pubertal) and 42-day-old (post-pubertal) female rats were subcutaneously injected with DHEA (60 mg/kg body weight) daily for up to 21–30 days. The post-pubertal model showed a steady increase in ovary weight and the number of ovarian cysts as well as uterine weight and thickness, which may be key features of PCOS, compared with the pre-pubertal model. Therefore, a post-pubertal PCOS model induced by DHEA may be an improved model to investigate the etiology of PCOS and development of therapeutic interventions.